2010
DOI: 10.1097/ico.0b013e3181ca31fc
|View full text |Cite
|
Sign up to set email alerts
|

Modified Osteo-Odonto Keratoprosthesis-The Indian Experience-Results of the First 50 Cases

Abstract: MOOKP is the keratoprosthesis of choice in bilateral end-stage ocular surface disorders in the Indian subcontinent. Complications do occur and have to be recognized and treated early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 14 publications
1
44
1
Order By: Relevance
“…The procedure by itself is a demanding and time consuming one, and takes up to 4-6 months towards completion of all stages. The results of the procedure are encouraging, especially given the good long-term retention of the prosthesis in these eyes [1,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 83%
“…The procedure by itself is a demanding and time consuming one, and takes up to 4-6 months towards completion of all stages. The results of the procedure are encouraging, especially given the good long-term retention of the prosthesis in these eyes [1,[7][8][9][10].…”
Section: Discussionmentioning
confidence: 83%
“…Iyer et al (2010) have reported an anatomic success of 96% but functional success of visual acuity >/¼20/60 in 66% in 50 eyes of 47 patients who underwent modified OOKP procedure in bilateral end stage ocular surface disease. The complications they encountered were oroantral fistula (6%), trophic mucosal alterations (8%), lamina exposure (central 6% and peripheral 8%), mucous membrane overgrowth (2%), hypotony (2%), expulsion of optic cylinder (4%), endophthalmitis (2%), glaucoma (20%), sterile vitritis (6%), and retinal detachment (2%).…”
Section: Discussionmentioning
confidence: 96%
“…66 Historical series have reported incidence rates ranging from 0e10%, with many studies below 5%. 2,3,10,15,47,49,51,63,65,76,79 A more recent series found a higher rate of 14.3% in a cohort of 83 eyes. 36 No associations with initial diagnosis, comorbidities, or other risk factors have been identified.…”
Section: Sterile Vitritis/uveitismentioning
confidence: 94%
“…46 There is often near complete restoration of visual acuity with appropriate treatment. 49,65 Recovery may take 2e10 weeks. 65,92 Prophylactic topical prednisolone acetate does not prevent sterile vitritis.…”
Section: Sterile Vitritis/uveitismentioning
confidence: 99%
See 1 more Smart Citation